Communication in industry by using the PROFINET protocol - Mulaosmanović, Adnan M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper is about the PROFINET communication used in industry for the purposes of communication between different elements within systems of monitoring and control of production processes. The PROFINET protocol is based on industrial Ethernet and allows the use of TCP / IP standards, which allows big business benefits during the life cycle of a manufacturing plant. Also, PROFINET is based on all the experiences with PROFIBUS, and goes a step further in its flexibility, improving performances. PROFINET enables the integration of various control equipment from the factory level to the control level. The concept of PROFINET satisfies all the requirements of industrial automation, and can be used for process automation that requires quick response time, i.e. the time below 100ms. For the purposes of other applications such as synchronized motion control,it enables a response time of less than 1 ms, and for safety applications it is possible to use PROFIsafe which is integrated into PROFINET. Introduction Industrial systems themselves are very complex so it is inevitable to divide them into parts that complement each other and communicate via protocols which will be discussed in this paper. The basic requirement of an industrial automation system is work in real time as well as reliability, unlike a business network where the primary conditions are high throughput and low operating costs. Fieldbus Fieldbus is a name that describes a modern industrial digital communication system designed to replace the existing current and voltage analog signals. The design and implementation of projects with a lot of cabling is quite complex as well as their maintenance. A different approach is therefore needed so the transition from analogue to digital methods of data transfer has started,  since digital methods also provide greater accuracy than traditional analog signals. PROFINET standard PROFINET satisfies all the requirements placed before it in automation technology,  no matter whether it is manufacturing plant automation, process automation  or machinery automation. It has already been used in the auto industry as a standard technology for a long time. Also, PROFINET is in use in other industries such as machine industry, food industry, packaging and logistics, and every day more and more is in use in other industries such as shipbuilding and railways. PROFINET versions In PROFINET, there are two function classes independent from each other, PROFINET IO and PROFINET CBA. The distributed field devices are connected through the PROFINET IO. Also, it uses three diferent communication channels to exchange data with the control systems and other devices. For Non real time (NRT) purposes, the standard TCP/IP chanel is used for parameterization, configuration and acyclic read/write operations. The real time (RT) chanel is used for standard cyclic data transfer and alarms. Isochronous real time (IRT) is a high speed chanel used for motion control applications. The PROFINET CBA concept is designed for the distributed industrial automation applications, and it is suitable for component-based machine-to-machine communication via TCP/IP and for real time communication required for modular plant design. Conformance classes The range of functions of PROFINET IO is divided into well-organized conformance classes (CC). These conformance classes provide a practical summary of various minimum properties. There are three conformance classes that build upon one another and are oriented to typical applications.These classes are CC-A, CC-B and CC-C. Cabling Specificic working conditions in which devices operate in industrial production require components that are a lot more resilient than devices operating in office conditions. PROFINET cabling is based on the link End-to-End, which is specified in IEC 61784-5-3. PROFINET defines a one-to-one straight connection. Copper cables and optical fibers are available for connection of network nodes. All cables must meet the requirements of a planned automation project. Network nodes parameters For proper work of network nodes, appropriate parameters for individual network nodes have to be assigned. These parameters include a device name and an IP address. New equipment does not have a device name, only a MAC address, which is globally unique and cannot usually be modified. Network components Only units with switch functionality are allowed as signal distributors for PROFINET. A switch is a layer 2 device which complieswith ISO/IEC 15802-3:1988 standard, and it receives data packets at its ports and forwards them selectively. It can also send and receive different data simultaneously at all ports. Conclusion As it can be seen, PROFINET represents a number of improvements in industrial communications. At the level of major production systems with a growing number of PLCs and PC computers that communicate with each other and with the rest of the IT system by exchanging large amounts of data, PROFINET  shows to be a much better solution than PROFIBUS. PROFINET is based on industrial Ethernet.
Keywords: PROFINET; Networks; industry; Automation